Un sistema bioclimático para el pronóstico de la sigatoka negra en plátano - Jiménez Otárola, Francisco (1993)
The relationship between accumulated rainfall duration and the infection level of leaf number four of the plantains was used to construct a bioclimatic forecasting system of the black Sigatoka disease (Mycosphaerella fijiensis). This system permits the determination of the most opportune timing for fungicide applications. The systems is simple, has a predictive character of two weeks and has been tested with success under field conditions in Turrialba, Costa Rica